C PROGRAM AS A TOOL FOR THE TEACHING OF SECOND ORDER ORDINARY DIFFERENTIAL EQUATION - Amin, Harahap; -, Zahedi; Enos, Lolang; Ansoruddin, Ansoruddin; Wingkolatin, Wingkolatin; Efendi, Efendi (PATTIMURA UNIVERSITY, 2024)
Second order ordinary differential equation (ODE) has many applications in science and engineering. Undergraduate students in science and engineering departments must study this subject in order to understand other subjects which are related to real applications they will encounter later. There are many excellent textbooks on differential equations where the students can study the theory and solve the problems. However, a textbook cannot give a quick answer for a problem particularly when the problem is quite difficult. A good choice is to use software such as Maple or Mathematica. However, this software is not always available for the teaching and purchasing it is usually beyond the ability of a student or even a lecturer. On the other hand, lecturers who want to create problems by themselves will follow the theory of the ODE. While creating the problems may not be difficult, answering them are harder. Problems which are very easy to answer are less worthless because they will not increase the students’ knowledge. Here comes the solution. A C program has been created to help lecturers create problems and solve them quickly. The program is interactive and can be easily understood by anyone who has basic theory of ODE. No knowledge of programming is needed; a user just runs it and follows the instruction. Students can also use the program to sharpen their knowledge. They can compare the solution of a problem they have solved with the answer given by the program. While commercial software such as Maple and Mathematica is very powerful, they cannot be used without writing necessary commands to solve a problem.